SERVICE EXCELLENCE, DAMPAK DAN PENGARUHNYA TERHADAP KEPUASAN PELANGGAN DAN LOYALITAS PELANGGAN - Muhammad Supriyanto (Epicheirisi: Jurnal Manajemen, Administrasi, Pemasaran dan Kesekretariatan, 2019)
The purpose of this article is to convey the influence and impact of excellent service on customer satisfaction and loyalty. Excellent service is one of the efforts made by the company to serve customers as well as possible, so as to provide satisfaction to customers and meet the needs and desires of customers, both in the form of products or services. Excellent service is the best service provided by the company to meet the expectations and needs of customers, both customers within the company and outside the company. In excellent service there are two interrelated elements, namely service and quality. Both elements are very important to be considered by service personnel (salespeople, traders, waiters, or salesmen). Quality Service (Service Excellence) can create satisfaction and can create customer loyalty without going through customer satisfaction. The concept of excellent service can be applied to various organizations, agencies, governments, or business companies.